CRONOLOGÍA DE ERUPCIÓN DE LOS DIENTES PERMANENTES EN NIÑOS Y NIÑAS DE 5, 6 Y 7 AÑOS (2010)
Objective: To determine de age of eruption of the first permanent molar (6), central (1) and lateral (2) incisors and to stablish the eruption sequence in a group of children ranging from 5, 6 and 7 years of age.Methods: An observational descriptive cross sectional study based on a sample of 900 Colombian children was done. They were examined with mouth mirror and probe under adequate illumination for the status of the eruption of the teeth mentioned. Additionally, their weight and height was registered to calculate the Body Mass Index. Means, modes, medians and standard deviation were determined for all data. Bivariate analyses were performed by Student’s t and Mann Whitney U test.Results: The lower right central incisor (41) and the lower left central incisor (31) were the teeth that appeared more frequently in 544 and 543 children, respectively. The sequence of eruption varied according to sex and the eruption of permanent teeth was earlier in boys than girls by a minimum difference. The first tooth to erupt in males was the lower right central incisor (4l) and the first lower right molar (46) in females.Conclusion: The first tooth erupted at 6 years 11 months (lower central incisor) and the latest was the upper lateral incisor at 7 years 5 months. The eruption sequence both in males and females was 6, 1, 2 for the maxilla. For the mandible, it was 1, 6, 2 for males and 6, 1, 2 for the females.